Liquidity and International Trade - Antonio Rodriguez-Lopez (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper introduces a framework to study the links between the supply of liquid assets for the financial market and the international allocation of economic activity. Private assets' liquidity properties - their usefulness as collateral or media of exchange in financial transactions - affect assets' values and interest rates, with consequences on firm entry, production, aggregate productivity, and total market capitalization. In a closed economy, the liquidity market increases the size and productivity of the sector of the economy that generates liquid assets. In an open economy, however, cross-country differences in financial development|as measured by the degree of liquidity of a country's assets - generate an allocation of real economic activity that favors the country that supplies the most liquid assets. In such a setting, trade liberalization magnifies the gap in economic activity between the countries.
Keywords: E43; E44; F12; F40; 330; liquidity; trade; financial development; interest rates